2002
DOI: 10.1016/s0550-3213(02)00274-2
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological bounds on neutrino degeneracy improved by flavor oscillations

Abstract: We study three-flavor neutrino oscillations in the early universe in the presence of neutrino chemical potentials. We take into account all effects from the background medium, i.e. collisional damping, the refractive effects from charged leptons, and in particular neutrino self-interactions that synchronize the neutrino oscillations. We find that effective flavor equilibrium between all active neutrino species is established well before the big-bang nucleosynthesis (BBN) epoch if the neutrino oscillation param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
501
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(521 citation statements)
references
References 41 publications
16
501
4
Order By: Relevance
“…Because of the near bi-maximal mixing paradigm emerging for the neutrino mass matrix, more stringent constraints can be placed on the neutrino lepton number since asymmetries in the more poorly constrained mu and tau flavors can be converted to an asymmetry in the more stringently constrained electron neutrinos through synchronized flavor transformation [17]. However, even the strongest constraint available, on the electron neutrino lepton number, allows |L e | 1 MeV < ∼ 0.1 at the epoch of nucleosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the near bi-maximal mixing paradigm emerging for the neutrino mass matrix, more stringent constraints can be placed on the neutrino lepton number since asymmetries in the more poorly constrained mu and tau flavors can be converted to an asymmetry in the more stringently constrained electron neutrinos through synchronized flavor transformation [17]. However, even the strongest constraint available, on the electron neutrino lepton number, allows |L e | 1 MeV < ∼ 0.1 at the epoch of nucleosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of redistribution of initially large lepton asymmetry by the oscillations was calculated in ref. [29], for more related references and analytical calculations see review [12]. It has been shown that for weak mixing (LOW solution for the solar neutrino anomaly) the redistribution of leptonic numbers is insignificant, as is presented in fig.…”
Section: Neutrino Oscillations In the Early Universementioning
confidence: 93%
“…3. As a result, the following quite restrictive bound on asymmetry of all neutrino flavours can be obtained [29]:…”
Section: Neutrino Oscillations In the Early Universementioning
confidence: 99%
“…Cosmological constraints on the neutrino degeneracy parameter began to be analyzed at the end of the past century (see, for example: Lesgourgue & Pastor 1999;Pastor & Lesgourgue 2000;Lesgourgue & Liddle 2001;Orito et al 2002;Dolgov et al 2002b). A relic neutrino degeneracy leads to a different amount of neutrinos and antineutrinos.…”
Section: Degenerate Fermions That Decouple When They Are Ultra-relatimentioning
confidence: 99%
“…In this work we will deal with fully degenerate fermionic dark matter. Semidegenerate massive neutrinos, with different degrees of degeneracy, have been extensively addressed; see, for example, Freese et al (1983); Kang & Steigman (1992); Lesgourgues & Pastor (1999); Lesgourgues & Liddle (2001); Dolgov et al (2002b);and Dolgov (2002a).…”
Section: Introductionmentioning
confidence: 99%